Some new Ostrowski type fractional integral inequalities for generalized relative semi-(r; m, h)-preinvex mappings via Caputo k -fractional derivatives - Kashuri,Artion (Universidad Católica del Norte, Departamento de Matemáticas, 2019)
Abstract: In the present paper, the notion of generalized relative semi-(r; m, h)-preinvex mappings is introduced and some new integral inequalities for the left-hand side of Gauss-Jacobi type quadrature formula involving generalized relative semi-(r; m, h)-preinvex mappings are given. Moreover, some new generalizations of Ostrowski type integral inequalities to generalized relative semi-(r; m, h)-preinvex mappings that are (n + 1)-differentiable via Caputo k-fractional derivatives are established. Some applications to special means are also obtain. It is pointed out that some new special cases can be deduced from main results of the article.